A multilevel nonvolatile visible light photomemory based on charge transfer in conformal zinc–tin oxide/Au nanoparticle heterostructures. Issue 21 (20th May 2022) - Shih, Li-Chung; Lin, Sheng-Rong; Chaurasiya, Rajneesh; Kung, Po-Yen; Jhang, Song-Syun; Liu, Bernard Haochih; Su, Yen-Hsun; Chen, Jen-Sue
Abstract : A photomemory based on a ZTO/Au NP heterostructure is revealed. It exhibits a broad spectral response and great retention to visible light due to the charge transfer at the ZTO/Au NP interface and surface plasmon resonance (SPR) of Au NPs. Abstract : Optical data processing and storage have become a promising stage for next-generation communication and computation technologies. Rather than using electrical bias in traditional memories, photomemories driven by optical signals have the ability to store light information directly, which is advantageous for the improvement of the power efficiency of optical data processing systems. Herein, a novel oxide transistor based photomemory with a channel layer comprising Au nanoparticles (NPs) embedded in a zinc–tin oxide (ZTO) film is explored, which simultaneously has a visible light sensing and data storage ability. The ZTO/Au NP heterostructure facilitates electron transition between ZTO and Au NPs via the localized surface plasmon resonance (LSPR) and modulation of the Schottky barrier width using visible light (405, 520, and 635 nm) and gate bias co-stimulation. Accordingly, the ZTO/Au NP photomemory exhibits high responsibility, multilevel data storage with excellent retention (>10 4 s), and ∼100 cycles of writing/reading/erasing/reading (WRER) cycle switching in response to the visible light stimuli. The ZTO/Au NP photomemory highlights the potential for both photonic signal detectivity and storage, which will be highly desirable in future optoelectronic technologies.